2021
DOI: 10.1001/jamasurg.2021.2373
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Efficacy of Neoadjuvant Chemoradiotherapy Plus Surgery for the Treatment of Locally Advanced Esophageal Squamous Cell Carcinoma

Abstract: IMPORTANCEThe prognosis of patients with locally advanced esophageal squamous cell carcinoma (ESCC) remains poor after surgery. Neoadjuvant chemoradiotherapy (NCRT) has been shown to potentially improve survival.OBJECTIVE To compare the treatment efficacy of NCRT plus surgery with surgery alone for long-term survival among patients with locally advanced ESCC. DESIGN, SETTING, AND PARTICIPANTSThe Neoadjuvant Chemoradiotherapy for Esophageal Cancer 5010 study was a multicenter open-label randomized phase 3 clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 29 publications
1
116
0
Order By: Relevance
“… [45] , [46] , [47] One newly published trial that only reported short-term outcomes with one year's follow up was excluded, [45] while two trials from our included studies (the NEOCRTEC5010 trial [5] and the CROSS trial [6] ) with updated long-term outcomes were included in the analysis. [ 46 , 47 ] Supplementary figure 12 summarized the network meta-analysis of OS on all included patients [ [9] , [10] , [11] , [12] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , 46 , 47 ], ESCC subpopulation [ [9] , [10] , [11] , [12] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , 46 , 47 ], and EAC subpopulation. [ [9] , [10] , [11] , 27 , 34 , 44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [45] , [46] , [47] One newly published trial that only reported short-term outcomes with one year's follow up was excluded, [45] while two trials from our included studies (the NEOCRTEC5010 trial [5] and the CROSS trial [6] ) with updated long-term outcomes were included in the analysis. [ 46 , 47 ] Supplementary figure 12 summarized the network meta-analysis of OS on all included patients [ [9] , [10] , [11] , [12] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , 46 , 47 ], ESCC subpopulation [ [9] , [10] , [11] , [12] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , 46 , 47 ], and EAC subpopulation. [ [9] , [10] , [11] , 27 , 34 , 44 …”
Section: Resultsmentioning
confidence: 99%
“…[45À47] One newly published trial that only reported short-term outcomes with one year's follow up was excluded, [45] while two trials from our included studies (the NEO-CRTEC5010 trial [5] and the CROSS trial [6]) with updated long-term outcomes were included in the analysis. [46,47] Supplementary figure 12 summarized the network meta-analysis of OS on all included patients [9À12,27À43,46,47], ESCC subpopulation [9À12,27À43,46,47], and EAC subpopulation. [9À11, 27,34,44,47] Here, network meta-analysis on OS in all included patients shows that NCRT is superior to NCT (HR: 0¢83, 95%CrI: 0¢69À0¢99) and surgery (HR: 0¢72, 95%CrI: 0¢63À0¢82).…”
Section: Subgroup Analysis and Sensitivity Analysismentioning
confidence: 99%
“…Although it is not difficult to conclude from the CROSS trial that the effects of nCRT on SCC seem larger than AC, it is hard to widely extrapolate this result because of the small fraction of SCC patients. The recently published NEOCRTEC5010 trial randomized 451 patients with SCC to receive either nCRT plus surgery or surgery alone [13]. The results showed that nCRT improved the 5-year survival compared to surgery alone group (59.9% vs. 49.1%, p = 0.025), which was more favorable than those of the CROSS trial [13].…”
Section: Neoadjuvant Chemoradiotherapymentioning
confidence: 99%
“…The recently published NEOCRTEC5010 trial randomized 451 patients with SCC to receive either nCRT plus surgery or surgery alone [13]. The results showed that nCRT improved the 5-year survival compared to surgery alone group (59.9% vs. 49.1%, p = 0.025), which was more favorable than those of the CROSS trial [13]. Moreover, the R0 resection rate was higher in the nCRT group than surgery alone (98.4% vs. 91.2%, p = 0.002) and the pCR rate reached 43.2%.…”
Section: Neoadjuvant Chemoradiotherapymentioning
confidence: 99%
See 1 more Smart Citation